High-temperature-resistant brake pad friction material

By adding secondary composite binder and sepiolite powder to the friction material of the brake pad, the metal sulfide with high melting point is solved, and the problem of thermal decay of traditional brake pad materials at high temperatures is improved, and the stability and resistance of the friction coefficient are improved. High temperature performance.

CN119242065APending Publication Date: 2025-01-03JIANGSU FANGYI AUTOPART MANUFACTURE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411388190.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Traditional asbestos brake pad materials friction under high temperature conditions produce heat decay, resulting in attenuation of friction coefficient, affecting braking efficiency and safety performance.

Method used

Using a high-temperature resistant brake pad friction material, the matrix phenolic resin is added with secondary composite binder, plant fiber, sepiolite powder and friction performance regulator, and wet granulation and hot pressing technology are used to form high-quality Metal sulfide at melting point improves the overall high temperature resistance of the material.

Benefits of technology

The softening temperature and friction coefficient stability of friction materials are significantly improved, the thermal fading problem is improved, and the stable braking performance under high temperature conditions is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of brake pad friction materials, in particular to a high-temperature-resistant brake pad friction material which comprises the following components in parts by mass: 6-10 parts of matrix phenolic resin, 10-15 parts of a secondary composite binder, 15-20 parts of plant fibers, 8-12 parts of sepiolite powder, 15-20 parts of filler and 8-12 parts of a friction performance regulator. According to the high-temperature-resistant brake pad friction material, the material preparation uniformity is creatively improved through the granulation technology, a surface bonding structure can be introduced into the friction material through the secondary composite binder, the overall melting point is higher than that of phenolic resin, and evenly-distributed metal sulfide can be generated under the high-temperature condition; therefore, the overall high-temperature resistance of the friction material is improved, the softening temperature of the friction material is increased, the long-acting and stable friction coefficient is obtained, and the heat fading problem is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brake pad friction materials, and in particular to a high temperature resistant brake pad friction material. Background Art

[0002] Brake pad friction material is a key component in the braking system, directly affecting braking efficiency and safety performance; traditional asbestos brake pad materials, under partial heavy load or long braking scenarios, friction generates high temperatures that can lead to severe thermal degradation of the friction material.

[0003] Thermal decay resistance is the ability of friction materials to resist the decay of tribological properties when working at high temperatures. Brake pad friction materials should have good thermal decay resistance to ensure stable driving of the car during continuous braking or high-temperature braking. The high temperature generated by braking friction will soften the matrix and cause local micro-melting, resulting in insufficient bite force between the original friction material and the mating surface, which manifests as a decay of the friction coefficient.

[0004] Therefore, avoiding the softening of the friction material at high temperature is crucial to maintaining the stability of the friction coefficient, so it is necessary to improve the high temperature resistance of the friction material. In view of this, we propose a high temperature resistant brake pad friction material. Summary of the invention

[0005] The purpose of the present invention is to solve the deficiencies mentioned in the above background technology and provide a high temperature resistant brake pad friction material.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A high temperature resistant brake pad friction material, the mass fractions of the components of the friction material include: Base phenolic resin: 6-10 parts; Secondary composite adhesive: 10-15 parts; Plant fiber: 15-20 parts; Sepiolite powder: 8-12 parts; Filler: 15-20 parts; Friction performance modifier: 8-12 parts.

[0007] Preferably, the preparation method of the friction material is: Step 1: Mix and stir the base phenolic resin, plant fiber, sepiolite powder, filler and friction performance regulator in proportion, spray a wetting liquid during the stirring process, and prepare spherical friction particles by wet granulation; Step 2: Mix the undried spherical friction particles with the secondary composite binder, wrap the secondary composite binder on the surface of the spherical friction particles, put the spherical friction particles wrapped with the secondary composite binder into a hot press for hot pressing, and finally perform heat treatment to obtain a solidified brake pad friction material.

[0008] Preferably, the wetting liquid is a 5-8wt% corn starch solution, and the mass fraction of the wetting liquid used accounts for 20-35% of the total mass of the base phenolic resin, plant fiber, sepiolite powder, filler and friction performance regulator in step one.

[0009] Preferably, the secondary composite binder comprises phenolic resin, tin powder and sulfur in a mass ratio of 1:0.5-1:1-2.

[0010] Preferably, the mass ratio of the tin powder to sulfur is 1:1-2.

[0011] Preferably, the hot pressing molding is provided with a pressure of 10-15 MPa, a hot pressing temperature of 150-180° C., and a pressure holding time of 10-15 min.

[0012] Preferably, the plant fiber raw material is rape straw fiber, and the plant fiber preparation method is: Step 1: Soak rape straw fiber in water for 24-30 hours, crush it into 40-60 mesh short fibers by a crusher, and then dry it to constant weight; Step 2: Soak the chopped fibers in a 1wt% NaOH solution, setting the ratio of the chopped fibers mass to the NaOH solution volume to 1:30g / mL, and soak for 30-60 minutes; Step 3: Wash until the pH is neutral, and dry again to constant weight to obtain alkali-treated plant fibers.

[0013] Preferably, the filler is one or more of alumina, silicon dioxide, calcium carbonate, aluminum silicate, and vermiculite powder.

[0014] Preferably, the friction performance modifier is one or more of flake graphite, petroleum coke, zinc stearate, and friction powder.

[0015] Compared with the prior art, the present invention has the following beneficial effects: This high-temperature resistant brake pad friction material creatively improves the uniformity of material preparation through granulation technology, and can introduce a surface bonding structure into the friction material through a secondary composite binder, so that the overall melting point is higher than that of phenolic resin, and can produce uniformly distributed metal sulfides under high temperature conditions, thereby improving the overall high-temperature resistance of the friction material, increasing the softening temperature of the friction material, and then obtaining a long-lasting and stable friction coefficient, improving the thermal decay problem. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. In the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0017] The present invention describes the above technical solution in detail through the following embodiments: Example 1

[0018] A high temperature resistant brake pad friction material, the mass fractions of the components of the friction material include: Phenolic resin 2123-1T: 8 parts; Secondary composite adhesive: 12 parts; Rapeseed straw fiber: 20 parts; Sepiolite powder: 10 parts; 325 mesh alumina powder: 17 parts; Type 195 flake graphite: 12 parts.

[0019] In this embodiment, the secondary composite binder specifically includes phenolic resin, tin powder and sulfur in a mass ratio of 1:1:2, and the mass ratio of tin powder to sulfur is 1:2, that is, 3 parts of phenolic resin 2123-1T, 3 parts of tin powder and 6 parts of S-80 type sulfur powder; The base phenolic resin of this embodiment is purchased from Hebei Zetian Chemical Industry, which sells phenolic resin products with the brand of 2123-1T, wherein free phenol is ≤2.5% and the fineness is 200 mesh; the base phenolic resin of this embodiment adopts phenolic resin 2123-1T, which is the same product as the phenolic resin in the secondary composite binder, for the convenience of distinction; sepiolite powder is purchased from Shijiazhuang Leisheng Mineral Products Co., Ltd., with a 2-2.5g / cm 3 Specification; Type 195 flake graphite was purchased from China Graphite Group Co., Ltd., alumina powder was purchased from Zhengzhou Xinli Wear-Resistant Materials Co., Ltd. and sold in 4000# specification; 325 mesh tin powder was purchased from Beijing Yi Jin New Materials Technology Co., Ltd., and sulfur was purchased from Qingdao Luchuan Chemical Co., Ltd. and sold in 400 mesh S-80 type sulfur powder.

[0020] Phenolic resin has a low melting point, which is the reason why it is necessary to improve high temperature resistance. When the braking friction temperature rises, the friction material containing the resin base softens, which leads to the problem of low friction coefficient. Therefore, it is considered to increase the melting point of the friction material during the heating process, that is, to add high melting point components so that it can reduce the softening thermal decay problem when high temperature is generated by braking. The tin powder and sulfur in this embodiment have higher melting points than phenolic resin. At the same time, sulfur can react with metal tin powder to form sulfide and disulfide under high temperature conditions. Therefore, the amount of sulfur in this embodiment needs to be slightly more than that of metal tin powder. The formed sulfide and disulfide have a high melting point of more than 500°C, and have hard and wear-resistant physical properties. They can form friction fillers again under high temperature vulcanization reaction to improve the friction coefficient, thereby achieving high temperature resistance and reducing the obvious impact of thermal decay of traditional phenolic resin.

[0021] The plant fiber raw material is rape straw fiber, and the plant fiber preparation method is as follows: Step 1: Soak rape straw fiber in water for 24 hours, put it into a plowshare mixer for mixing, set the main shaft speed to 700r / min, and the stirring blade speed to 1400r / min, process for 5 minutes to obtain loose fiber material without obvious agglomeration, crush it into 40-60 mesh short-cut fiber by a crusher, and then dry it to constant weight; Step 2: Soak the chopped fibers in a 1wt% NaOH solution, setting the ratio of the chopped fibers mass to the NaOH solution volume to 1:30g / mL, and soak for 60 minutes; Step 3: Wash until the pH is neutral, and dry again to constant weight to obtain alkali-treated plant fibers.

[0022] Because plant fibers generally contain a large number of hydroxyl groups on their surfaces, they are polar and hydrophilic, but phenolic resins and secondary composite binders are non-polar and hydrophobic. The compatibility between the two is poor, which will lead to poor bonding and affect the overall performance of the material. Therefore, they need to be modified to reduce their own polarity and hydrophilicity. Alkaline solutions can dissolve the non-cellulose components in the fibers that are polar and hydrophilic, thereby improving compatibility and bonding.

[0023] Sepiolite powder has a porous structure, which can produce a good interface effect between the sepiolite powder and other components. At the same time, this structure is conducive to the adhesion of the wetting liquid during the granulation process, showing good wettability, and then can be used as a granulation nucleation material, which is conducive to obtaining a more uniform granulation effect and quality.

[0024] Specifically, the method for preparing the friction material of this embodiment is as follows: Step 1: Mix and stir the base phenolic resin, plant fiber, sepiolite powder, filler and friction performance regulator in proportion, spray a wetting liquid during the stirring process, and prepare spherical friction particles by wet granulation. The wetting liquid in this embodiment adopts a 5wt% corn starch solution, and the mass fraction of the wetting liquid used accounts for 30% of the total mass of the plant fiber, sepiolite powder, filler and friction performance regulator in step 1; through granulation, the fiber with a large difference in appearance from other powder raw materials can be wrapped in the spherical particles, thereby improving the fluidity of the raw materials and facilitating the acquisition of stable molding quality; Step 2: Mix the undried spherical friction particles with the secondary composite binder, wrap the secondary composite binder on the surface of the spherical friction particles, put the spherical friction particles wrapped with the secondary composite binder into a hot press for hot pressing, control the pressure of 15MPa, the hot pressing temperature of 1180℃, and keep the pressure for 15min; because the position of the secondary composite binder is wrapped on the surface of the spherical friction particles, after molding, it is shown that there is a secondary composite binder at the joint, and because the secondary composite binder has a high-temperature vulcanization reaction process, the overall material can be better connected based on this reaction; Step 3: Heat treatment is performed to obtain the solidified brake pad friction material. In order to completely solidify and eliminate the residual stress and thermal stress inside the friction material after hot pressing, and prevent the pressed product from deformation, warping, etc., it is placed in a drying oven, kept at 140°C for 1 hour, heated to 160°C for 3 hours, and then continued to heat to 180°C for 6 hours. The friction material is naturally cooled to room temperature to obtain the friction material.

[0025] Example 2

[0026] The difference between this embodiment and embodiment 1 is that in this embodiment, 3 parts of tin powder and 3 parts of S-80 type sulfur powder are provided, and other conditions are the same.

[0027] Example 3

[0028] The difference between this embodiment and embodiment 1 is that in this embodiment, 3 parts of tin powder and 10 parts of S-80 type sulfur powder are used, and other conditions are the same.

[0029] Example 4

[0030] The difference between this embodiment and embodiment 1 is that in this embodiment, vermiculite powder is used instead of sepiolite powder, and other conditions are the same.

[0031] Comparative Example 1

[0032] The difference between this comparative example and Example 1 is that in this comparative example, no tin powder and sulfur are provided in the secondary composite binder, and only 12 parts of phenolic resin 2123-1T are used instead, and other conditions are the same.

[0033] Comparative Example 2

[0034] The difference between this comparative example and Example 1 is that no sepiolite powder is added in this comparative example, and other conditions are the same.

[0035] Samples were prepared according to the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 2, and the friction coefficient and wear amount were tested at 100° C., 200° C., and 350° C.; The specific test method is: Friction coefficient: Use MMW-1A universal friction and wear testing machine to grind and polish the surface of the test block to ensure that the material surface is smooth and flat, and select a pressure load of 30N, a speed of 200r / min, and a friction time of 10min; the small thrust ring sample is made of 32GrMn steel, with a dual diameter of 28mm, and the effective average value is obtained after 5 tests; Wear amount: measured by the mass loss of the test block per unit time, using a turntable speed of 330r / min, wearing on the turntable for 180min, weighing the wear amount as a percentage of the original mass after the continuous test at 100℃-350℃ is completed; The specific data is as follows:

[0036] According to the data in the above table, in Examples 1 to 3, the contents of tin powder and sulfur powder have an impact on the high temperature resistance of the friction coefficient. If the proportion of sulfur powder is reduced, the thermal attenuation becomes slightly larger, but the friction coefficient is also at a higher level. However, excessive sulfur powder does not further significantly improve the high temperature resistance, and the wear amount remains slightly fluctuating. Note that the friction coefficient brought by replacing sepiolite powder with vermiculite powder is higher, but the wear amount is similar in use. However, in the preparation process, it is found that the preparation yield of Example 4 is low, the granulation is difficult, which is not conducive to nucleation granulation, resulting in poor hot pressing quality, cracks in the finished product, and the wear rate is higher than that of the porous structure of sepiolite. Considering that it is also caused by poor molding, Example 4 does not meet the actual production needs, so sepiolite powder is preferred, which has good granulation molding effect and stable product quality. From the data of Comparative Examples 1 and 2, it can be seen that if phenolic resin 2123-1T is used directly, it will lead to obvious thermal decay problems, and the faster the decay is, the more obvious it is as the temperature rises. The data of the embodiment can be used to show that tin powder and sulfur components can effectively improve the high temperature resistance; the decay caused by sepiolite powder is within the normal range, and its comprehensive performance after the loss of friction filler is also better than that of Comparative Example 1; In summary, Example 1 can be preferred as an implementation scheme.

[0037] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A high temperature resistant brake pad friction material, characterized by: The mass fractions of the components of the friction material include: Base phenolic resin: 6-10 parts; Secondary composite adhesive: 10-15 parts; Plant fiber: 15-20 parts; Sepiolite powder: 8-12 parts; Filler: 15-20 parts; Friction performance modifier: 8-12 parts.

2. The high temperature resistant brake pad friction material according to claim 1, characterized in that: The preparation method of the friction material is as follows: Step 1: Mix and stir the base phenolic resin, plant fiber, sepiolite powder, filler and friction performance regulator in proportion, spray a wetting liquid during the stirring process, and prepare spherical friction particles by wet granulation; Step 2: Mix the undried spherical friction particles with the secondary composite binder, wrap the secondary composite binder on the surface of the spherical friction particles, put the spherical friction particles wrapped with the secondary composite binder into a hot press for hot pressing, and finally perform heat treatment to obtain a solidified brake pad friction material.

3. The high temperature resistant brake pad friction material according to claim 2, characterized in that: The wetting liquid is a 5-8wt% corn starch solution, and the mass fraction of the wetting liquid used accounts for 20-35% of the total mass of the base phenolic resin, plant fiber, sepiolite powder, filler and friction performance regulator in step one.

4. The high temperature resistant brake pad friction material according to claim 2, characterized in that: The secondary composite adhesive comprises phenolic resin, tin powder and sulfur in a mass ratio of 1:0.5-1:1-2.

5. The high temperature resistant brake pad friction material according to claim 4, characterized in that: The mass ratio of the tin powder to sulfur is 1:1-2.

6. The high temperature resistant brake pad friction material according to claim 2, characterized in that: The hot pressing molding is provided with a pressure of 10-15 MPa, a hot pressing temperature of 150-180° C., and a pressure holding time of 10-15 minutes.

7. The high temperature resistant brake pad friction material according to claim 1, characterized in that: The plant fiber raw material is rape straw fiber, and the plant fiber preparation method is: Step 1: Soak rape straw fiber in water for 24-30 hours, crush it into 40-60 mesh short fibers by a crusher, and then dry it to constant weight; Step 2: Soak the chopped fibers in a 1wt% NaOH solution, setting the ratio of the chopped fibers mass to the NaOH solution volume to 1:30g / mL, and soak for 30-60 minutes; Step 3: Wash until the pH is neutral, and dry again to constant weight to obtain alkali-treated plant fibers.

8. The high temperature resistant brake pad friction material according to claim 1, characterized in that: The filler is one or more of alumina, silicon dioxide, calcium carbonate, aluminum silicate and vermiculite powder.

9. The high temperature resistant brake pad friction material according to claim 1, characterized in that: The friction performance regulator is one or more of flake graphite, petroleum coke, zinc stearate and friction powder.